Development of Early Childhood Education Teacher Competency: Reviewed from Perception and Teacher's Motivation - Ni Gusti Ayu Made Yeni Lestari; Mohamad Syarif Sumantri; Nurbiana Dhieni (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
The purpose of this study was to describe the perceptions and motivations of kindergarten teachers regarding early childhood educator’s competency development. This study used a qualitative approach with a descriptive method. Data was collected through the distribution of questionnaires presented in google form format and enriched through in-depth interviews. The subjects in this study were 55 kindergarten teachers spread across Bali province. The data analysis technique of this research used the development of Miles and Huberman. The results of the study showed that teacher knowledge about educator’s competency was still lacking in depth. Most of the teachers considered the competence of educators only having ability in teaching. Based on perception, teachers who had certified competency have positive perception toward development of early childhood education. In terms of motivation, all teachers have high motivation in developing competence as early childhood education educators. Teachers who have been certified to improve the quality of learning lead to training in child development tasks, and certified teachers in addition to insight and skills in teaching are also preparation for participating in PPG programs in the future. The perception and motivation of early childhood education educators will greatly impact the quality of learning provided to early childhood. For this reason, early childhood education teachers must continue to be active and participatory in participating in various teacher competency development programs.